2002
DOI: 10.1002/joc.855
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting features of Asian summer monsoon during surplus and deficient rainfall over India

Abstract: An endeavour is made to distinguish the mean summer monsoon features during surplus and deficient monsoon seasons. Based on all-India summer monsoon rainfall, over 42 years , seven surplus and ten deficient monsoon seasons are identified. Making use of daily averaged (00 Z and 12 Z) reanalysis data sets from the National Center for Environmental Prediction-National Center for Atmospheric Research for the corresponding surplus and deficient monsoon seasons, the mean circulation characteristics and large-scale e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Saji and Yamagata (2003a) confirmed that the IOD affects the ISMR. Raju et al (2002) stressed the role of Western Indian warming during the positive IOD event in the modulation of the ISMR. In another recent study, Ashok et al (2004a) showed, by use of observed datasets and an AGCM, the importance of the western pole of the IOD in modulating the rainfall over the northwest regions of India and neighboring Pakistan, and in reducing the impact of ENSO on Indian summer rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Saji and Yamagata (2003a) confirmed that the IOD affects the ISMR. Raju et al (2002) stressed the role of Western Indian warming during the positive IOD event in the modulation of the ISMR. In another recent study, Ashok et al (2004a) showed, by use of observed datasets and an AGCM, the importance of the western pole of the IOD in modulating the rainfall over the northwest regions of India and neighboring Pakistan, and in reducing the impact of ENSO on Indian summer rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…It provided for the first time a unique database to examine climate variability of circulation features and energetics of the monsoon. Recent studies (ANNAMALAI et al, 1999;SPERBER et al, 2000;RAJU et al, 2002) conducted making use of the NCEP reanalysis, confirm the usefulness of these data sets. As a result, understanding the dynamical mechanisms of the monsoon variability in time-scales ranging from weeks to years is an issue of considerable importance.…”
Section: Introductionmentioning
confidence: 81%
“…162, 2005 Climatological Features of the Asian Summer Monsoon 1517 (1997). Further, RAJU et al (2002) stated that on a seasonal scale the NCEP precipitation appears to be reliable as regards the distribution of rainfall over India.…”
Section: Precipitation Olr and Net Tropospheric Moisturementioning
confidence: 99%
“…The budget equations are obtained from the prognostic and diagnostic equations of an atmospheric model based on simple mathematical transformations and represented in flux form with pressure as the vertical coordinate (Raju et al, 2002). In this study, the time-mean large-scale balance equations are bifurcated into stable mean and transient eddy parts.…”
Section: Methodsmentioning
confidence: 99%